Pemetaan Zonasi Daerah Rawan Kebakaran Hutan Berbasis Sistem Informasi Geografis (SIG) di Kawasan Taman Nasional Kerinci Seblat - Fikri, Husnul; Prarikeslan, Widya (Lembaga Yasin AlSys, 2024)
This study aims to determine the zoning level of vulnerability and the distribution of forest fire prone areas in the TNKS SPTN Region III Painan Resort Kambang. This research uses descriptive method with quantitative approach. Data analysis techniques used are scoring and overlay. The results showed 1) The level of forest fire vulnerability there are two classes of vulnerability, low class of 173,015.62 hectares generally located in the rain forest. Medium class 115,14.76 hectares are in primary and secondary dryland forest areas, fields, dryland farms, rice fields and shrubs.2) The distribution of fire-prone areas there are a total of 31 hotspots, moderate category 24 points are in dryland farms mixed with shrubs and fields, high category 6 points are in rainforest areas and dryland farms mixed with shrubs, for low category 1 point is in the rainforest area. Based on this data, it can be concluded that most of the forests in Kambang Resort are in the medium and low vulnerability class zones.